Conversational Structure Analysis in Conflict Zone Interview - Agung Meidiarto (Talenta Publisher, 2021)
The researcher analyzed the conversational structure in the conflict zone interview. The aspects that the researcher examined were opening, closing, adjacency pairs, turn-taking allocation, and repair strategies by using theories of Schegloff and Sack, the data of this descriptive qualitative study were classified into three rules (R1, R2 and R3) of turn-taking allocation namely R1(current-select-next), R2(next speaker self-selects), and R3(no-current-speakerselect- next & no-next-speaker-self-selects) and four strategies of conversational repair: SISR(self-initiated self-repair),OISR (other-initiated self-repair), SIOR(self-initiated other repair), and OIOR(other-initiated other-repair The researcher collected the data by downloading and transcribing the video. The research found that the opening of this conversation used the greeting-thank sequences. In the closing section,the interviewer ensured there was no information left and then closed by saying thanks and pleasure. Regarding turn taking allocation based on Sacks. R1 appeared 231 times, R2 appeared 22 times and R3 didn’t appear. In the conflict zone interview, there were 4 combinations of adjacency pairs. There were combinations of questions –answers with 54 pairs, information-response with 8 pairs, statement-confirmation with 55 pairs, and greeting-thank with only 1 pair. Then, there are 4 types of conversational repair found in the conversation. The type of repair that dominates in the conversation was Self-Initiated Self-Repair(SISR) which appeared 45 times. Self-Initiated Other-Repair (SIOR) appeared 3 times, and Other-Initiated Self-Repair (OISR) appeared with 11 times.And then,the last one is Other-Initiated Other-Repair (OIOR) was not found at all.